CONDITIONS OF FORMATION OF INTEREST IN EDUCATIONAL EXPERIMENTAL WORK IN GRADUATES PEDAGOGICAL GYMNASIUMS - Kravtsova, І.А. (Pedagogy of Higher and Secondary Education, 2000)
The formation of the research interest may by effective enough if the close connection of the educational-cognitive and educational-research activities of pupils. Depending on the profound, process and reasons side of educational-research work didactic conditions must by organized by considerations of opportunities, abilities, and experience of pupils educational-cognitive activities,